FIXED-DOSE COMBINATION VERSUS SEPARATE ANTITUBERCULOSIS FORMULATIONS IN PULMONARY TUBERCULOSIS PATIENTS: EVALUATION OF EFFECTIVENESS AND SAFETY - Sitepu, Rimenda; Ascobat, Purwantyastuti; Ekasari, Flora; Instiaty, Insti (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to compare the effectiveness and safety of fixed dose combination (FDC) versus separate (separate formulation [SF]) antituberculosis (TB) formulations in patients with bacteriologically confirmed pulmonary TB. Methods: Data were collected retrospectively from patient records, which included all newly diagnosed bacteriologically confirmed pulmonary TB patients treated with first category FDC or SF between January 2014 and January 2017 at the Dr. Esnawan Antariksa Hospital. The efficacy of the formulations was determined according to acid-fast bacilli (AFB) sputum smear conversion at the end of the intensive phase (month 2), after 6 months of therapy, and after the extended treatment phase (month 3). Adverse drug reactions (ADRs) during treatments were recorded as safety outcomes. Chi-square tests were used to analyze the differences between the groups. Results: On comparing patients treated with FDC (n=33) and SF (n=30), rates of sputum conversions did not differ significantly after 2 months (83.3% vs. 78.7%, p=0.693) and the intensive phase was extended by 1 month for patients with conversion failures at this time point. One of seven patients in the FDC group did not achieve sputum conversion during the extended phase and was recorded as a medication failure. At the end of continuation phase, all other subjects achieved sputum conversion. The overall frequencies of ADRs were not significantly higher in the FDC group than that in the SF group (36.4% vs. 23.3%, p=0.260). Conclusion: No differences in effectiveness and safety profiles were identified between first category FDC and separate anti TB formulations.